SOCIO-ECONOMIC SIGNIFICANCE OF ECOTOURISM DEVELOPMENT - Xolmurodova , Moxichehra (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The transition from extractive mass tourism to sustainable ecotourism frameworks represents a fundamental paradigm shift in regional economic development strategies. Evaluating the precise socio-economic vectors of this transition remains challenging due to methodological difficulties in quantifying informal economic retention and community-level socio-cultural preservation. This study investigates the socio-economic impact of ecotourism integration within heritage-rich and semi-arid regional economies, specifically focusing on the decentralized hospitality sector and local artisanal networks. Utilizing a mixed-methods empirical design, including structured socio-economic surveys (n = 520) and econometric modeling across three selected ecological corridors, the research evaluates income multipliers, employment generation capabilities, and sociocultural disruption indices. Statistical analysis indicates that community-based ecotourism enterprises demonstrate a 68.4% local income retention rate, vastly outperforming conventional transnational hotel chains. Regression models reveal a strong positive correlation between ecotourism cluster development and rural household income stabilization (R2 = 0.74, p < 0.001). Consequently, aligning regional development policy with localized ecotourism initiatives is practically indispensable for achieving long-term demographic stability. The findings validate the hypothesis that localized eco-travel infrastructures directly mitigate poverty-driven urban migration by establishing robust, sustainable rural micro-economies. Integrating environmental stewardship with direct financial incentives provides a replicable economic architecture for developing regions. Strategic resource allocation toward grassroots tourism initiatives yields substantially higher long-term socioeconomic dividends than heavily subsidized, large-scale tourist infrastructures.